Word imageability is associated with expressive vocabulary in children with autism spectrum disorder. (March 2022) - Lin, Kimberly R; Wisman Weil, Lisa; Thurm, Audrey; Lord, Catherine; Luyster, Rhiannon J
Background & aims: Throughout typical development, children prioritize different perceptual, social, and linguistic cues to learn words. The earliest acquired words are often those that are perceptually salient and highly imageable. Imageability, the ease in which a word evokes a mental image, is a strong predictor for word age of acquisition in typically developing (TD) children, independent of other lexicosemantic features such as word frequency. However, little is known about the effects of imageability in children with autism spectrum disorder (ASD), who tend to have differences in linguistic processing and delayed language acquisition compared to their TD peers. This study explores the extent to which imageability and word frequency are associated with early noun and verb acquisition in children with ASD. Methods: Secondary analyses were conducted on previously collected data of 156 children (78 TD, 78 ASD) matched on sex and parent-reported language level. Total expressive vocabulary, as measured by the MacArthur Bates Communicative Development Inventory (MB-CDI), included 123 words (78 nouns, 45 verbs) that overlapped with previously published imageability ratings and word input frequencies. A two-step hierarchical linear regression was used to examine the relationship between word input frequency, imageability, and total expressive vocabulary. An F-test was then used to assess the unique contribution of imageability on total expressive vocabulary when controlling for word input frequency. Results: In both the TD and ASD groups, imageability uniquely explained a portion of the variance in total expressive vocabulary size, independent of word input frequency. Notably, imageability was significantly associated with noun vocabulary and verb vocabulary size alone, with imageability explaining a greater portion of the variance in total nouns produced than in total verbs produced. Conclusions: Imageability was identified as a significant lexicosemantic feature for describing expressive vocabulary size in children with ASD. Consistent with literature on TD children, children with ASD who have small vocabularies primarily produce words that are highly imageable. Children who are more proficient word learners with larger vocabularies produce words that are less imageable, indicating a potential shift away from reliance on perceptual-based language processing. This was consistent across both noun and verb vocabularies. Implications: Our findings contribute to a growing body of literature describing early word learning in children with ASD and provide a basis for exploring the use of multisensory language learning strategies.